Activation of Mitochondrial Protein Phosphatase SLP2 by MIA40 Regulates Seed Germination. Issue 2 (6th December 2016) - Uhrig, R. Glen; Labandera, Anne-Marie; Tang, Lay-Yin; Sieben, Nicolas A.; Goudreault, Marilyn; Yeung, Edward; Gingras, Anne-Claude; Samuel, Marcus A.; Moorhead, Greg B.G.
Abstract : The serine/threonine protein phosphatase SLP2 is mitochondrial intermembrane space localized and redox activated by the oxidoreductase Mia40. Abstract: Reversible protein phosphorylation catalyzed by protein kinases and phosphatases represents the most prolific and well-characterized posttranslational modification known. Here, we demonstrate that Arabidopsis ( Arabidopsis thaliana ) Shewanella -like protein phosphatase 2 (AtSLP2) is a bona fide Ser/Thr protein phosphatase that is targeted to the mitochondrial intermembrane space (IMS) where it interacts with the mitochondrial oxidoreductase import and assembly protein 40 (AtMIA40), forming a protein complex. Interaction with AtMIA40 is necessary for the phosphatase activity of AtSLP2 and is dependent on the formation of disulfide bridges on AtSLP2. Furthermore, by utilizing atslp2 null mutant, AtSLP2 complemented and AtSLP2 overexpressing plants, we identify a function for the AtSLP2-AtMIA40 complex in negatively regulating gibberellic acid-related processes during seed germination. Results presented here characterize a mitochondrial IMS-localized protein phosphatase identified in photosynthetic eukaryotes as well as a protein phosphatase target of the highly conserved eukaryotic MIA40 IMS oxidoreductase.